PENINGKATAN PRESTASI BELAJAR MENYIMAK PADA PEMBELAJARAN TEMATIK INTEGRATIF MELALUI MULTIMEDIA INTERAKTIF PADA SISWA SEKOLAH DASAR (Universitas Ahmad Dahlan, 2018)
The purpose of this research is to know the application of interactive multimedia, improvement of learning achievement, and the advantages of interactive multimedia. This research use desciptive qualitative approach. The subjects studied were the students of grade 1, amounting to 24 people. The type of research used is classroom action research (PTK) with data collection techniques through test, observation, and documentation. This data analysis technique using data analysis with interactive model, and in the analysis and data collection activities using 2 cycles that is cycle I and cycle II. The result of the research shows that there is an increase of learning achievement by using interactive multimedia in integrative thematic learning with the value of â¥70 as much as 80% of students, student cooperation with the provision of â¥75 80% and student motivation with the value of â¥75 as much as 80%. So it can be seen the advantages of interactive multimedia is to make learning more fun, can improve the achievement listening integrative thematic learning, foster student potential, improve student cooperation. While the shortage is a long time in preparation and require the availability of facilities.Â Â Â Â Â